Appropriate stage of ripeness and time for vacuum frying of cultivated banana - Pitak, Lakkana; Wongpichet, Saree (Engineering and Applied Science Research, 2014)
This paper aims to study appropriate ripeness of cultivated banana and time period for vacuum fry. Sliced bananas of thickness 1-2 mm were fried at temperature 130 ๐C under vacuum condition. The samplings were done at 3 level of ripeness; 1) raw banana, 2) the first day of ripeness, 3) the second day of ripeness. In addition 5 levels of fried period were set; 6, 8, 10, 12, 14 min. The raw banana fried for 12 min shown the best result. The products have a crisp texture, appropriate hardness and toughness, standard moisture and color with the most acceptance by consumers.